Penerapan Manajemen Mutu Ekstrakurikuler Karya Ilmiah di SMA Muhammadiyah 1 Taman Sidoarjo - M. Nashiiruddin Addaa’i; Akhtim Wahyuni (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2020)
The success of extracurricular activities depends on quality or quality management or management processes. Therefore, this study aims to describe the application of quality management for extracurricular activities of teenage scientific papers including planning, implementation and evaluation activities in order to get customer satisfaction, be able to optimize aspects of everyone, carry out fact-based management and make continuous improvements. The research method used is descriptive qualitative research through observation, interviews and documentation. This research was conducted at SMA Muhammadiyah 1 Taman, which one of the visions is excellent academic quality. The application of extracurricular quality management of youth science consists of planning activities including customer involvement in the selection of supervisors to planning work programs that can be carried out and always carrying out joint evaluations, implementing activities including the involvement of each student in scientific competitions at regional, national and international levels, as well as evaluation activities. through discussion and project improvement and more intensive coaching. The application is adjusted to the quality management principle of Edward Sallis known as total quality management, namely customer satisfaction, aspects of everyone, management based on facts and continuous improvement which results in increased extracurricular achievements of scientific work in scientific competitions that are followed. The conclusion of this study is the application of extracurricular quality management of youth science consisting of planning, implementation and evaluation activities on the basis of quality management in the form of customer satisfaction, aspects of everyone, fact-based management and continuous improvement.